Analysis of Single Nucleotide Polymorphisms of STK32B, PPARGC1A and CTNNA3 Gene With Sporadic Parkinson's Disease Susceptibility in Chinese Han Population - Shi, Chang-he; Cheng, Yuan; Tang, Mi-bo; Liu, Yu-tao; Yang, Zhi-hua; Li, Fang; Fan, Yu; Yang, Jing; Xu, Yu-ming (Frontiers in Neurology, 2018)
Recently, 5 novel SNPs (single nucleotide polymorphisms), rs10937625 in STK32B (serine/threonine kinase 32B), rs17590046 in PPARGC1A (peroxisome proliferator-activated receptor gamma coactivator 1-alpha), and rs12764057, rs10822974, and rs7903491 in CTNNA3 (catenin alpha 3), were found to be associated with increased risk of essential tremor (ET) in a GWAS (genome-wide association study)in individuals of Caucasian ancestry. Considering the overlap between ET and Parkinson's disease (PD) in pathological features and clinical manifestations, a case-control study comprising 546 PD patients and 550 control subjects was carried out to examine whether the same variants were also associated with PD in Chinese Han population. However, the above variants did not show an association with PD. Our results suggested that these variants do not play a major role in PD in the Chinese population, Actually, the clinical overlap between PD and ET is under debate. In our Chinese Han cohort, we did not verify potential genetic pleiotropy between two diseases, which may indicated that etiology and pathobiology of PD and ET are distinct. Thus, a more comprehensive study such as a multi-center study may be helpful to evaluate the relationship between the 5 new susceptible loci and PD in Chinese Han population in the future.